2019
DOI: 10.1002/14651858.cd005522.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol for osteoarthritis

Abstract: Background Tramadol is o en prescribed to treat pain and associated physical disability in osteoarthritis (OA). Due to the pharmacologic mechanism of tramadol, it may lead to fewer associated adverse e ects (i.e. gastrointestinal bleeding or renal problems) compared to non-steroidal anti-inflammatory drugs (NSAIDs). This is an update of a Cochrane Review originally published in 2006. Objectives To determine the benefits and harms of oral tramadol or tramadol combined with acetaminophen or NSAIDs in people with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 64 publications
0
48
0
2
Order By: Relevance
“…5 The prevalence of knee OA among elderly in China is nearly 30%. 6 Conventional treatment of knee OA mainly aims at alleviation of pain including pharmacological, such as non-steroidal antiinflammatory drugs (NSAIDs) [7][8][9][10][11][12][13][14][15] and non-pharmacological managements 11,13 . NSAIDs are associated with a moderate effect on pain relief.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The prevalence of knee OA among elderly in China is nearly 30%. 6 Conventional treatment of knee OA mainly aims at alleviation of pain including pharmacological, such as non-steroidal antiinflammatory drugs (NSAIDs) [7][8][9][10][11][12][13][14][15] and non-pharmacological managements 11,13 . NSAIDs are associated with a moderate effect on pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs are associated with a moderate effect on pain relief. 9,10 However, evidence on their effectiveness is limited, 9-12, 14,15 and often associated with undesirable side effects. 11,14,15 Recent review showed that appropriate treatments for knee OA included biomechanical interventions, intra-articular corticosteroids, exercise (land-based and water-based), self-management and education, strength training, and weight management.…”
Section: Introductionmentioning
confidence: 99%
“…5 The prevalence of knee OA among elderly in China is nearly 30%. 6 Conventional treatment of knee OA mainly aims at alleviation of pain including pharmacological, such as non-steroidal antiinflammatory drugs (NSAIDs) [7][8][9][10][11][12][13][14][15] and non-pharmacological managements 11,13 . NSAIDs are associated with a moderate effect on pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs are associated with a moderate effect on pain relief. 9,10 However, evidence on their effectiveness is limited, 9-12, 14,15 and often associated with undesirable side effects. 11,14,15 Recent review showed that appropriate treatments for knee OA included biomechanical interventions, intra-articular corticosteroids, exercise (land-based and water-based), self-management and education, strength training, and weight management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation